EXPERIENCES OF ADOLESCENT WOMEN WHO MARRIED AT AN EARLY AGE IN THE PAYA PASIR DISTRICT OF MEDAN MARELAN - Wellina BR Sebayang; Ida Yustina; Nurmaini Nurmaini; Kintoko Rochadi; Fikarwin Zuska (International Journal of Midwifery Research, 2023)
Cases of early marriage are a problem in various countries including Indonesia. Early marriage has an impact on reproductive health and risks experiencing emergencies during pregnancy and childbirth. Early marriage also tends to make children lose their right to play and get an education. The purpose of this study was to explore the experiences of young women who married at an early age in Paya Pasir Village, Medan Marelan District. The research design used was a qualitative phenomenological research design. The participants in this study were 10 married young women in the Paya Pasir sub-district . The results showed several sub-themes , namely: The causes of early marriage are due to romantic relationships, arranged marriages and economic factors, all participants did not have the mental readiness to face marriage. Experience in intercourse tends to mention surrender because of obligation and not enjoy. During pregnancy, two participants experienced an unexpected pregnancy, and even planned to have an abortion but it didn't happen. The contraceptive used by the participants was of the hormonal type, and all experienced symptoms of severe side effects. Experience in caring for babies all participants have felt anxiety, sadness and crying.